2015
DOI: 10.1016/j.jcf.2014.08.008
|View full text |Cite
|
Sign up to set email alerts
|

Long-term treatment with oral N-acetylcysteine: Affects lung function but not sputum inflammation in cystic fibrosis subjects. A phase II randomized placebo-controlled trial

Abstract: NAC recipients maintained their lung function while placebo recipients declined (24 week FEV1 treatment effect=150 mL, p<0.02). However no effect on HNE activity and other selected biomarkers of neutrophilic inflammation were detected. Further studies on mechanism and clinical outcomes are warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
63
0
4

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(70 citation statements)
references
References 35 publications
3
63
0
4
Order By: Relevance
“…Corticosteroids [97] Ibuprofen* [92,[102][103][104] Antibacterials with anti-inflammatory properties Azithromycin* [109] Anti-PcrV antibody (KB-001A) [111] Modulators of intracellular signaling IL-10 [144] Interferon-γ (actimmune) [120] P38 MAPK inhibitor L-arginine [124] Parthenolide [145] Simvastatin [122] Synthetic triterpenoids (CDDO) [126] Thiazolidinediones/pioglitazone [116] Inhibitors of neutrophil influx Anti-IL-8 [146] Anti-IL-17 [ Anti-oxidants N-acetyl cysteine [139,140], β-carotene, glutathione, Omega-3 fatty acids Vitamin C, vitamin E [147] Anti-proteases α1-protease inhibitor (plasma derived and transgenic) [132] DMP-777 [148] EPI-hNE4 (Depalstat) [149] Monocyte/neutrophil elastase inhibitor [150] Recombinant secretory leukoprotease inhibitor [151] * Drugs recommended by CFF.…”
Section: Broad-based Anti-inflammatory Modulators Piroxicammentioning
confidence: 99%
See 1 more Smart Citation
“…Corticosteroids [97] Ibuprofen* [92,[102][103][104] Antibacterials with anti-inflammatory properties Azithromycin* [109] Anti-PcrV antibody (KB-001A) [111] Modulators of intracellular signaling IL-10 [144] Interferon-γ (actimmune) [120] P38 MAPK inhibitor L-arginine [124] Parthenolide [145] Simvastatin [122] Synthetic triterpenoids (CDDO) [126] Thiazolidinediones/pioglitazone [116] Inhibitors of neutrophil influx Anti-IL-8 [146] Anti-IL-17 [ Anti-oxidants N-acetyl cysteine [139,140], β-carotene, glutathione, Omega-3 fatty acids Vitamin C, vitamin E [147] Anti-proteases α1-protease inhibitor (plasma derived and transgenic) [132] DMP-777 [148] EPI-hNE4 (Depalstat) [149] Monocyte/neutrophil elastase inhibitor [150] Recombinant secretory leukoprotease inhibitor [151] * Drugs recommended by CFF.…”
Section: Broad-based Anti-inflammatory Modulators Piroxicammentioning
confidence: 99%
“…The study was of short duration and not powered to detect changes in pulmonary function or other clinical outcome measures. A subsequent large randomized double-blind placebo controlled trial demonstrated that N-acetyl cysteine stabilized lung function but had no effect on neutrophil elastase activity or other inflammatory biomarkers [140]. N-acetyl cysteine is converted to cysteine, an essential precursor of glutathione synthesis.…”
Section: Inhibition Of Neutrophil Influx and Neutrophil Productsmentioning
confidence: 99%
“…Notably, the use of the oral antioxidant N-acetylcysteine showed beneficial effects in CF lung disease through reduction of NE activity, associated with increased or stable lung function Conrad et al, 2015). More specifically, therapies targeting neutrophil proteases using aerosolized protease inhibitors as AAT (α-1 antitrypsin) or SLPI were tested in clinical trials in CF patients.…”
Section: Neutrophil-based Targeting Strategies and Their Implicationmentioning
confidence: 99%
“…However, clinical studies aiming to neutralize free NE activity in CF airways by the delivery of antiproteases, such as α-1 antitrypsin, showed modulated airway inflammation but failed to show convincing effects on lung function [25]. In contrast, the use of the oral antioxidant N -acetylcysteine, as a strategy to rebalance antioxidant deficiencies in CF, shows beneficial effects on lung function, but has no effect on neutrophilic inflammation [140]. Future studies are required to reconcile these findings and to further assess the therapeutic potential of antiprotease or antioxidant approaches in CF lung disease [24,141].…”
Section: Novel Therapeutic Conceptsmentioning
confidence: 99%